Social Innovation Promoting Policy and its Implementation in the European Union - Tamošiūnas, Teodoras (Socialiniai tyrimai, 2018)
Research problem: the paper deals with the following problem questions: In which EU documents and how is the policy of promoting social innovation emphasised? How is the policy of promoting social innovation implemented in the EU? Research subject: EU social innovation promotion policy and its implementation.Research aim: to analyse EU social innovation promoting policy and its implementation.Research methods: Content analysis and generalisation of EU strategic documents, legislation and information materials, case studies of implementation of social innovation.In the European Union, innovation promoting policy is developed through strategic and legal regulation documents adopted in EU institutions. Investments into fundamental research dominate, the importance of application of innovations for the growth of the economy of the country is emphasised, and a broad concept of innovations is applied, encompassing the implementation of innovations in business and public sector. However, innovation promoting policy and its implementation seldom put an emphasis on social innovations as an important part of the general system of innovations; the place and the importance of social innovations for the social environment of the society are given insufficient attention.According to the newest understanding of the European Commission, social innovation is new ideas that meet social needs, create new social relationships and develop new forms of collaboration. These innovations can be products, services or models, which meet unsatisfied social needs in a more efficient way. Social innovation is a means integrating various interested parties for the realisation of social needs. Such understanding of social innovations is closely linked with other concepts, oriented towards meeting social needs, such as social company, social entrepreneurship, social economics, and social policy experimentation.Social innovations are based on the ingenuity of the population, civic society organisations, local communities, institutions and companies. They also offer an opportunity for the public sector and all participants of the market to ensure that products and services correspond not only to the individual but also to collective aspirations. Stimulating innovation, entrepreneurship and knowledge society are the main EU policy directions in “Europe 2020” strategy. Social innovations differ from other innovations in that their main aim is to create social change. In comparison with the general concept of innovation, social innovations have an additional motive, which is social mission and social values.The authors of social innovations can come from all layers of society, from public or private sector or from non-governmental organisations. Most often the most valuable sources of new ideas come from collaboration of different sectors. Various groups can make valuable contributions to social innovations: these are businessmen, experts, politicians, representatives of communities and civic society. They can act on different levels: from new ideas and pilot projects to implement them to the formation of the new policy.Social innovations play a major role in EU cohesion policy. The topics of these innovations are oriented towards thematic targets in the five spheres of investment policy: 1) research and development, 2) employment, 3) education, 4) social policy, 5) strengthening administrative abilities.For the implementation of the model initiative “Innovation Union” of “Europe 2020” strategy, the European Commission has adopted a programme consisting of 10 measures. Group 9 of the mentioned measures emphasises the importance of social innovations. It is pointed out that the public sector has to improve the implementation of innovations in order to meet the expectations of the users of public services in a better way.In Europe, there are various examples of different social innovations: heart diseases prevention programmes meant for the whole society; social services to help lonely old-age people provided through the networks of neighbours; ecologic maps of cities that provide information for the local communities about the progress in decreasing pollution; ethical banks, which provide financial products in order to increase social benefits of innovations, etc. There are a lot of good ideas; however, the impact of social innovations is still insufficient. It is necessary to encourage experimenting. It is necessary to develop and disseminate new innovation creation and implementation methods that are superior to the existing practices. For that we need competent intermediaries, efficient incentives and networks, which would speed up and facilitate learning. There are such infrastructures all over Europe in the sphere of business innovations; however, their correspondent structures in the sphere of social innovations are insufficient. More exact methods of innovation evaluation are necessary, too.A bulletin of the outcomes of EU innovation implementation published by the European Commission in 2017 shows that the outcomes have improved for 15 countries, although there are major differences among these member states. In global terms, the EU is catching up with Canada and the USA, however, South Korea and Japan are ahead of it. Among foreign competitors, the most rapid progress is made by China. Within the EU, the leader of innovations is Sweden, followed by Denmark, Finland, the Netherlands, the UK and Germany. Lithuania is ascribed to the average innovators group; nevertheless, Lithuania is the most rapidly developing innovator. Lithuania moved from the 24th place in 2010 up to the 16th place in 2016 among the 28 EU member states. The growth of innovative developments in Lithuania during this period was the most rapid one and made up 21 percent.Since 2012, the European Commission has been announcing an annual contest of European social innovations, the number of applications ranging from 600 to 1,400. 30 applications with the best prospects are selected for the semi-finals, and then to the finals of 10 ideas, the teams of which are invited to develop these ideas in the social innovations centre in one of the member states. The members of the semi-finals get support for teaching and further development of their ideas, while three best ideas get prizes between 20,000 and 50,000 EUR. Besides, other social innovations contests are organised, too, e.g., “RegioStars” nominations and Social Innovations Tournament.The European Commission also performs direct financing of social innovations through EU investment programmes. It creates networks helping organizations all over Europe to join, learn from each other and share their experiences via the Social Innovations Community site. The conditions for social innovations and social companies in Europe are being improved; efforts are made to attract private investors. Information about the use of social innovations and methodologies of evaluating their outcomes is collected and disseminated. Incubatory structures meant for social innovations in Europe are supported and networks of EU incubators are created. Research is carried out, new ideas, programmes or spheres for social innovations are pursued, papers and articles on social innovations are published and stored.This scientific article is funded by the Research Council of Lithuania according to the project “Social innovation in the context of regional development: socioeconomic development of suburban (low urbanization level) territories and improving the quality of life” (2017–2018), registration No. TAP LB-17-012.
Keywords: social innovations; EU innovation promoting policy; social innovation implementation programmes